Interleukin-21 induces migration and invasion of fibroblast-like synoviocytes from patients with rheumatoid arthritis. (15th February 2016) - Xing, R; Jin, Y; Sun, L; Yang, L; Li, C; Li, Z; Liu, X; Zhao, J
Summary: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovial fibroblast hyperplasia and bone erosion. Fibroblast-like synoviocytes (FLS) play a pivotal role in RA pathogenesis through aggressive migration and matrix invasion, and certain proinflammatory cytokines may affect synoviocyte invasion. Whether interleukin (IL)-21 influences this process remains controversial. Here, we evaluated the potential regulatory effect of IL-21 on the migration, invasion and matrix metalloproteinase (MMP) expression in RA-FLS. We found that IL-21 promoted the migration, invasion and MMP (MMP-2, MMP-3, MMP-9, MMP-13) production in RA-FLS. Moreover, IL-21 induced activation of the phosphoinositide 3-kinase (PI3K), signal transducer and activator of transcription-3 (STAT-3) and extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) pathways, and blockage of these pathways [PI3K/protein kinase B (AKT) inhibitor LY294002, STAT-3 inhibitor STA-21 and ERK1/2 inhibitor PD98059] attenuated IL-21-induced migration and secretion of MMP-3 and MMP-9. In conclusion, our results suggest that IL-21 promotes migration and invasion of RA-FLS. Therefore, therapeutic strategies targeting IL-21 might be effective for the treatment of RA.